The determinants of bank's stability: A system GMM panel analysis - Thuy Tu Pham; Le Kieu Oanh Dao; Van Chien Nguyen (Cogent Business & Management, 2021)
This study was conducted to investigate the determinants of bank's stability in an emerging country. Data were collected from the commercial banks listed on Vietnam's Stock Exchanges over the years from 2010 to 2018. Further, the generalized method of moments (GMM) regression technique to control for the three sources of endogeneity, namely, unobserved heterogeneity, simultaneity and dynamic endogeneity are concerned. Results demonstrate that there exists a positive effect from banking sector indicators such as equity-to-asset ratio, bank size, loans-to-assets ratio, revenue diversification on the stability of bank. In addition, a possible finding deals with the positive influence of macroeconomic factors in the banking sector on bank's stability. Another possibility, bank's stability in the previous year often goes hand in hand with this of the current year. Further investigated on every presence of foreign investment in the banking system, total assets- based foreign investment also correlates positively with bank's stability. Finally, a negative effect from market share of mobilized capital, loan loss provisions, market structure on bank's stability can be found.
Keywords: B26; G21; G31; G32; M41; 650; Bank; foreign investment; GMM; stability; Zscore